Techniques of Melody Formation and Improvisation in Latvian Recitatives - Boiko Martin (Journal of Ethnology and Folkloristics)
The documentary material available for the study of recitatives (the dominant style of the older layer of Latvian folk song) mainly consists of field transcriptions from the late 19th and the first half of the 20th century. The material is fragmentary, although some of it when adequately read provides valuable insight into melody formation and improvisation. The study also points to findings in the rhythmic formation of Latvian recitatives, achieved through measurement of syllabic duration in audio recordings. A concept of melody formation techniques was developed, and two groups of techniques were identified: morphologic, and syntactic, each subdivided into an array of smaller groups of techniques. By defining and systematising these techniques it was possible to get a structured general picture of the melodics of Latvian recitatives as style. Some transcriptions made by Andrejs Jurjāns in the late 19th century and Emilis Melngailis in the 1920s, which extensively document the performance process (comprising a large number of transcribed melostrophes), indicate that in the solo sections of the melostrophe change of techniques was used as a method of improvisation. A procedure for indirectly detecting technique change has been developed by analysing and comparing early transcriptions.